Mathematical modelling of magnetising current surge of power transformers - Kutin, V. M.; Odrekhovskyi, V. B. (Visnyk of Vinnytsia Politechnical Institute, 2010)
The paper suggests a mathematical model for investigation of magnetising current surge (RMC) on connection of the power transformer to the network. It is shown, that calculative types of RMC can be exactly defined using the parameters of the system and saturative transformator. This mathematical model allows to compare tuning out of different relay from RMC and calculate parameters of protection operation according to the parameters of the system and transformer or characteristics of one-phase RMC.